カンキョウ ノ コトナル ヒョウガ チイキ ニ オケル セッピョウ シリョウ ノ デンキ デンドウド ト pH - 神山, 孝吉; カミヤマ, コウキチ; 藤井, 理行; フジイ, ヨシユキ; 渡辺, 興亜; ワタナベ, オキツグ; 山田, 知充; ヤマダ, トモミ; Kaminuma, Kokichi; Fujii, Yoshiyuki; Watanabe, Okitsugu; Yamada, Tomomi (1990)
P(論文) ネパール・パタゴニア・北極・南極地域からの雪氷試料を用いて, 融解後の電気伝導度とpHの値を比較検討した。試料の電気伝導度とpHは地域によって変動の範囲・平均値が異なっている。降雪に含まれる溶存イオン量が小さく電気伝導度の低い場合には, 地域に関わりなくほぼ一定のpH値を示す。しかし, 電気伝導度が増加するとともにpHが変動し, そこには地域的特徴が現れる。すなわち南極の海岸付近(昭和基地)・ネパール・パタゴニア地域では, 電気伝導度値が増加するのに伴ってpH値も増加しているが, 南極の内陸部では逆にpH値は減少している。原因としては海の直接的影響, 土壌圏の中和作用, 大気圏上層部での物質の取り込み過程, 火山活動, 人為的影響などが挙げられる。すなわち, 降雪系での物質輸送過程が重要な役割を担っていると考えられる。北極域グリーンランド及びスピッツベルゲン島において採取したコアには, 過去の電気伝導度とpHの値が記録されている。グリーンランド試料での値は, 南極内陸部と同様な傾向を示す。一方, スピッツベルゲン島の試料では値の変動幅が大きく, さまざまな環境変動の影響を受けてきたことを推測させる。スピッツベルゲン島のコア試料を深さごとに一定間隔で整理することによって, 各期間ごとの電気伝導度とpHの変動特性を明らかにした。この変動特性は, コア中の気泡を含んでいない氷の分布と一致していた。このような氷は過去の温暖な時期に形成されるので, 変動特性と合わせて物質輸送過程の変動を推定した。 Electrical conductivity (EC) and pH of melted snow and ice samples from Nepal, Patagonia, Arctic regions and Antarctica are compared. Most samples showed regional differences in means and ranges of EC and pH values. Low concentrations of dissolved substances, however, were accompanied by low ECs and approximately constant pH values, independent of the regions. Higher values of EC brought about regional pH differences. pH increased with higher EC values in coastal Antarctica (Syowa Station), Nepal and Patagonia. In contrast, pH decreased with the increased EC in snow from inland Antarctica. Ice cores from Greenland and in Spitsbergen provide records of EC and pH in snows of the past. The values of EC and pH in the Greenland samples are similar to those in the inland region of Antarctica. The values in the Spitsbergen samples vary widely, implying that they record a variety of past climatic events. A down core fluctuation of characteristics in the EC and pH distributions, is compared to core records in fixed intervals. The fluctuation coincides well with the profile of the clear ice ratio, which records melting events during warmer periods. The periodical variation in the transport process of substances in the precipitation system is estimated from the clear ice ratio and the characteristics of EC and pH. departmental bulletin paper